ANALISA PENGARUH NORMALIZING TERHADAP KEKERASAN BAJA PEGAS DAUN - Febriansyah, Muhammad; Junaidi , Ahmad; Sundari, Ella (MACHINERY Jurnal Teknologi Terapan, 2022)
Along with the development of people's lifestyles resulted in an increasing need for vehicles. In four-wheeled motorized vehicles, the suspension system is a very important part because it can affect the safety and comfort for the rider. The spring is the main component in the vehicle suspension which acts as a medium to receive dynamic loads from the road surface and vibrations on the wheels so that they are not transmitted to the vehicle frame directly and keep the wheels in contact with the road surface. the results of testing the raw material hardness specimens and specimens after normalizing, the average hardness of raw materials is 47.6 HRa, the specimens after normalizing at a temperature of 800° get an average hardness of 29.3 HRa, on the specimens the results after normalizing at a temperature of 850° get an average hardness of 35.3 HRa, the specimens after normalizing at a temperature of 900° get an average hardness of 41 HRa.